Halal logistics and supply chain management in Southeast Asia - Nor Aida Abdul Rahman; Azizul Hassan; Mohammad Fakhrulnizam Mohammad (Islamic business and finance series, 2021)
"The concept of Halal defines what adheres to Islamic law and is so comprehensive that it goes beyond food to include processes. The Halal industry has allowed many business firms a competitive advantage and is integral in its support for industries from food, tourism, banking, hospitality to medical. This book gives an overview of what Halal is in logistics and supply chain management and discusses related issues and challenges in Southeast Asia. The book also examines Halal logistics and supply chain in reference to global trends and practices. It attempts to integrate theoretical and methodological aspects of Halal logistics and supply chain study in different geographical areas across industries. This will be a useful reference for those who wish to understand the Halal ecosystem and Halal logistics supply chain development"